FILSAFAT ILMU SOSIAL PERSPEKTIF PANCASILAISME (Refleksi Kritis atas Konsep Filsafat Ilmu Ekonomi Pancasila Mubyarto) - Santoso, Heri (Jurnal Filsafat "WISDOM", 2009)
AbstractThe Economics philosophy of Pancasila was born as criticism of crisis occurred in neoclassical economics in Indonesia. Mubyarto identify the neoclassical economics crisis of historical, sociological, metaphysics, epistemological, and axiologicaldimension. Mubyarto offers the Economics philosophy of Pancasila as a solution by offering approach which more considering the sociological and historical dimension of Indonesian plurality. The economics philosophical assumptions must be relied on the philosophy and ideology of Pancasila, not based on liberal ideology.Although there are still any pro and contra opinion about the Economics philosophy of Pancasila, we can say that Mubyartohas succeeded to show the data and fact, identify causes of theIndonesian economics crisis, offer a solution for social sciencecrisis in Indonesia by the Economics philosophy of Pancasila. Inthe other side, Mubyartoâs Economics philosophy of Pancasilafaces obstacles, such as the lack of adequate response of othereconomic scientists, and no economics theory that is really constructed appropriates with the Indonesian socio-cultural condition.Keyword: Mubyarto, philosophy, social science, economics,Pancasila